Pengaruh Program Pengampunan Pajak Terhadap Efektivitas Penerimaan Pajak di Indonesia - Olivia Adam; Hartati Tuli; Siti Pratiwi Husain (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
This study aims at testing the influence of tax amnesty program toward the effectiveness of tax revenue at KPP in Indonesia. The data sources in this data are secondary data of tax revenue from all KPP in Indonesia in 2015 and 2016. The samples used in this data are tax revenue from 341 KPP offices. The data analysis methods are descriptive analysis and verification analysis. The hypothesis in this study is tested using paired sample t-test. It shows that tax amnesty does not significantly influence the effectiveness of tax revenue in KPP in Indonesia. The test reveals that out of 341 KPP offices, there are only 53 KPP offices (16%) whose tax revenue is effective, whereas the revenue from 288 KPP offices (84%) is not yet effective.